Simulation of GPR system operation using dipole antenna and AFW envelope detector technique for underground object detection application - Razali, Maryanti (2022)
Underground object detection requires a lot of time and energy and may damage the study surface area. Therefore, the use of electromagnetic wave reflection techniques emitted by GPR system to detect the embedded object is very useful. Beside wideband antenna, a narrowband antenna can be used in designing a GPR system using CST software. However, this type of GPR system produces blurry radargram image due to high ripple signal that occur in the antenna input signal. In this study, the design of GPR system simulations using CST software have been made using four frequency ranges which are from 0 – 0.13 GHz, 0.06 GHz – 0.08 GHz, 0 – 0.5 GHz and 0 – 1 GHz. The simulations also have been designed based on four depth of embedded object. Referring to the radargram image displayed by the design GPR system using frequency range 0 – 0.13 GHz, the embedded object has been clearly displayed in the radargram image which include the position of the object at 7 cm depth. On the other hand, by using frequency ranges 0 – 0.5 GHz and 0 – 1 GHz, the design GPR system has able to produce a clear radargram image showing embedded object position up to 20 cm depth. Furthermore, the design GPR system using frequency range 0.06 GHz – 0.08 GHz has produced a blurry radargram, but can be solved by applying the AFW envelope detector technique and produce a clear radargram image in detecting an embedded object position up to 7 cm depth. The results achieved through this study indicate that the use of narrowband antenna in GPR system is still able to detect an embedded object by applying an envelope detector technique which suggest an effective GPR system.